(untitled) (Tanzania Medical Journal, 2009)
Aim:To determine if impressions are disinfected prior to handling at the dental laboratory of the Muhimbili National Hospital. Materials and Methods: A retrospective survey of received impressions at the Dental Laboratory [June 2004 to May 2005] was obtained from the register. To determine the percentage of impressions disinfected prior to their handling, accompanying work authorization vouchers and a structured questionnaire were used. All four dental technicians who handled the received impressions were interviewed. Questions asked were on practice and attitudes and responses were on different point scales. Results are based on information gathered from the dental technicians. Results: Of the 1,453 impressions received none were reported to have been disinfected nor had disinfection been indicated on the accompanying work authorization prescriptions. The only protective gear worn by dental technicians was a laboratory coat and the known method of disinfection was placing of the taken impression under running water. Technicians were of the attitude that they should be responsible for ensuring impressions are disinfected prior to their handling. It was also agreed that a policy should be in place regarding disinfection of impressions prior to being handled and wearing protective gear should be compulsory. Conclusions: Within the limits of this study, it was observed that none of the received impressions were chemically disinfected prior to handling and a laboratory coat was the only protective gear worn and could pose a risk of cross contamination at the dental laboratory of the Muhimbili National Hospital. Tanzania Medical Journal Vol. 23 (2) 2008: pp. 14-15